A metal–organic gel‐based fluorescent chemosensor for selective Al3+ detection. (19th August 2019) - Gu, Dongxu; Yang, Weiting; Wang, Fuxiang; Li, Meiling; Liu, Lijuan; Li, Huihui; Pan, Qinhe
Abstract : As an important metal element, aluminium has a significant impact on the environment and human health, and thus the detection of Al 3+ has become the subject of much research. We synthesized a Ni(II)‐based metal–organic gel (Ni‐MOG), which can serve as an Al 3+ fluorescence sensor with high selectivity and sensitivity, the limit of detection being calculated to be 0.5 μM. In addition, a composite film was further fabricated by hybridization of this Ni‐MOG with poly(vinyl alcohol). The composite film produced a rapid fluorescence response to Al 3+ solutions at concentrations above 5 × 10 −5  M in 5 min. The Ni‐MOG composite film can also be successfully applied for the sensitive detection of Al 3+ in real samples of tap water and seawater. The effective detection of Al 3+ described in this contribution provides a new insight into water quality monitoring and has promising application value. Abstract : A Ni(II)‐based metal–organic gel (Ni‐MOG) was synthesized together with a composite film of the gel by combination with poly(vinyl alcohol), both of which can serve as Al 3+ fluorescence sensors with high selectivity and sensitivity.